Self-Discipline Makes Policy Advice Better - Gert G. Wagner (Wirtschaftsdienst, 2022)
Abstract There is a differentiated literature on policy advice, but it is largely disconnected from the literature (and the underlying research landscape) on academic communication, which originally dealt only with the natural sciences. And both strands of the discussion are barely connected to the figure of the „public intellectual“ who has played an important role in the humanities and social sciences for decades. This is a role that, as discussed in this article, is now played digitally by many scholars with low barriers to entry. This creates new problems, which can be addressed by research ethics. Of course, the relevant literature in communication studies is not discussed in detail in this article, but it is pointed out that (selective) examination of this literature might also be worthwhile with regard to policy advice.